ICT COMPETENCY MOOC : PIONEERING LARGE SCALE MOOC IN MALAYSIA - Emmy Dahliana, Hossain; Chuah, Kee Man; Johari, Abdullah; Ang, Tse Chwan; Rosita, Mohamed Othman (2019)
Introduction Universiti Malaysia Sarawak’s ICT Competency MOOC began 5 years ago in 2014 as one of the four pioneer MOOCs developed by public universities in the country for the Malaysia MOOCs project. The other three MOOCs are Islamic and Asian Civilizations (TITAS), Introduction to Entrepreneurship, and Ethnic Relations. The Malaysia MOOCs project is in line with Shift 9: Globalized Online Learning stated in the National Education Blueprint 2015-2015 (Higher Education). This MOOC was first named IT Literacy, but was later renamed to ICT Competency, to equip students with competency instead of just literacy in ICT. Also, incoming student intakes are found to have sufficient IT literacy before entering university, having learned the syllabus in school, and having more exposure to ICT. The first version of this MOOC has only 5 learning units (LUs), namely The Computer System, The Internet and WWW, Security and Ethics, Computational Thinking, and Open Source Technology. Today, after several revisions, the updated version of ICT Competency MOOC has 9 learning units: Overview of Computers and ICT, The Computer System, Communication and Networks, The Internet and WWW, Information Systems, Computational Thinking, Open Source Technology, Computer Security, Privacy and Ethics, and ICT Knowledge in Various Domains. Each learning unit contains three types of contents: lecture materials, quizzes, and ViFlections. Lecture materials consist of notes, videos, articles and other relevant materials that were both created and curated. ViFlection – a term coined by the UNIMAS MOOC team – is short for Video Reflection. ViFlections are scenario-based videos showing the life of local university students in dealing with ICT. To complete a unit, students need to watch the video and answer questions to help the characters solve their problems - this helps the students to reflect on what they have learned in the unit. During its first year, ICT Competency MOOC has 5,588 students from 70 countries.